Laparoscopic Management of Acute Pancreatitis Secondary to Rapunzel Syndrome - Bijan Koushk Jalali; Alperen Bingöl; Ashraf Reyad (Case Reports in Surgery)
A 17-year-old girl presented with bilious vomiting and abdominal pain to the surgery department. The history was positive for trichotillomania and trichophagia. A CT scan showed a mass in the stomach, which was highly suspicious for a gastric bezoar. Drooping parts of the bezoar caused a duodenal obstruction with secondary acute pancreatitis. The bezoar was removed via a laparoscopically performed gastrotomy.